Pengaruh Gaya Kepemimpinan dan Komunikasi terhadap Kinerja Karyawan dengan Motivasi Kerja Sebagai Variabel Intervening: Studi Kasus pada Aroma Bakery - Rio Ardiansyah Saragih; Feri Ardiansyah; Suci Etri Jayanti; Willy Cahyadi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study was conducted with the aim of evaluating the influence of leadership style and communication on employee performance, with work motivation as an intervening variable among employees of Aroma Bakery. The number of respondents in this study was 35 individuals. The sampling technique used was total sampling. This research is a causal-explanatory study, which explains the position of the variables studied as well as the influence between one variable and another. The data analysis used in this study is quantitative analysis using the Structural Equation Model (SEM) with SmartPLS. The results of the study show that: Leadership style has no effect on employee performance. Leadership style has no effect on work motivation. Communication has no effect on employee performance. Communication has no effect on work motivation. Work motivation has a significant effect on employee performance. Leadership style has no effect on employee performance with work motivation as an intervening variable. Communication has no effect on employee performance with work motivation as an intervening variable.